The Economics of Collective Bargaining - Bronfenbrenner, M. (Quarterly Journal of Economics, 1939)
Atomistic competition, 535. — Wage-fixing activity: no employer discrimination. The open shop, 538; the closed shop, 543. — Employer discrimination: quantity discrimination, 545; price discrimination, 548; discrimination of both types, 550. — Recapitulation, 550. — Plural price of labor: demand and supply curves independent, 551; demand curves dependent, 556; demand and supply curves inter-related, 559.